(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Magic water, pumpkin fritters, and tofu mousse are some of the healthiest foods and beverages that Organic Avenue promotes while maintaining a strong competitive edge in the vicinity. Organic Avenue, established in the second week of February 2023, located at Saranay Road, Barangay 171 Caloocan City, aims to promote Filipino culture by providing tasty, inexpensive food to people who like to eat on a budget. The marketing plan determines Organic Avenue’s target market by segmenting its demographic, geographic, psychographic, behavioral, and socio-economic characteristics. Organic Avenue established a marketing trend to be aware of market demand and create and advertise products and services to consumers in order to meet demand. Organic Avenue’s employees are assigned based on their skills, talents, and specialties, together with their corresponding duties and responsibilities in their positions. The result is healthy street food, an affordable price, an accessible place, marketing trends, and all types of consumers may be attracted. Organic Avenue has the potential to achieve its long-term objectives and can attract investors due to its projected favorable financial plan in terms of income statement, cash flow, and balance sheet.